Trigger-oriented HIV testing at Internal Medicine hospital Departments in Northern Italy: an observational study (Fo.C.S. Study). Issue 11 (1st December 2016) - Cerini, Carlo; Casari, Salvatore; Donato, Francesco; Porteri, Enzo; Rodella, Anna; Terlenghi, Luigina; Compostella, Silvia; Apostoli, Alessandra; Brianese, Nigritella; Urbinati, Lucia; Salvi, Andrea; Rossini, Angelo; et al.
Abstract: Background: Early detection of undiagnosed HIV infected patients is of paramount importance. The attitude of Italian hospital-based Internal Medicine physicians to prescribe HIV testing following the detection of HIV-associated signs, symptoms and behaviours (triggers) has been reported to be poor. The aim of the study is to quantify the extent of the missed opportunities for early HIV diagnosis in Internal Medicine Departments (IMD). Methods: Patients admitted to IMD of a General University Hospital in Italy in March–June 2013 were interviewed using a structured questionnaire investigating the presence of triggers for HIV testing, including patient's characteristics, symptoms and conditions associated with HIV infection. HIV tests performed during hospitalisation were recorded. Results: HIV testing was performed in 73 (6.6%) out of 1113 hospitalisations (1072 patients), providing positive results in three cases (4.1%). All of them presented ≥1 triggers. Conversely, 853 triggers were identified in 528 hospitalisations with at least one trigger (47.4%). The proportion of hospitalisations where an HIV testing was prescribed was 3.1%, 9.5% and 16.0% in the presence of zero, one-to-two or more triggers, respectively. Age <70 years, female gender, length of hospital stay, haematological disease, HBV infection, multiple sexual partners and lymphadenopathy were predictors of HIV testing by logistic regression analysis. Conclusions: Although chances of an HIV test being performed in patients hospitalised in IMD increases along with the number of triggers, the number of tests being performed in people presenting with triggers is unacceptably low and requires educational interventions in order to obtain individual and public health advantages.